Effects of angiotensin receptor–neprilysin inhibition on myocardial energy metabolism and prognosis in patients with acute myocardial infarction complicated by heart failure - Cheng, Caiming; Nie, Yu; Chen, Di; Yang, Yan; Liang, Shunji; Yu, Qin (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThis study aims to evaluate the effects of angiotensin receptor–neprilysin inhibitor (ARNI) on myocardial energy metabolism and prognosis in patients with acute myocardial infarction (AMI) complicated by heart failure (HF).MethodsA retrospective analysis was conducted on data from 244 inpatients admitted to our center, who were diagnosed with AMI complicated by HF. Among these patients, 210 completed a 1-year follow-up. According to the use of angiotensin-converting enzyme inhibitors (ACEI)/angiotensin receptor blockers (ARB)/ARNI, the 210 patients were divided into the ARNI group (107 cases, 51.0%) and the non-ARNI (ACEI/ARB) group (103 cases, 49.0%). The main outcome measures were the changes in myocardial energy expenditure (MEE) and prognostic indicators after 1-year follow-up.ResultsARNI significantly reduced MEE after 1 year compared with the ACEI/ARB [(129.61 ± 40.81) kcal/min vs. (154.49 ± 47.58) kcal/min, P < 0.01]. The MEE level in the HFrEF group was significantly higher than that in the HFmrEF group (P < 0.05). The ARNI group showed significantly lower rates of heart failure (23.0% vs. 43.4%, P = 0.001), recurrent myocardial infarction (9.8% vs. 22.1%, P = 0.009), and renal function deterioration (5.7% vs. 13.1%, P = 0.049) than those in the non-ARNI group. ROC analysis identified an MEE (kcal/min) cutoff value of 178, with 85% sensitivity and 64% specificity for the prediction of cardiac death (AUC = 0.74, P = 0.007). During the 1-year follow-up, patients with MEE over 178 kcal/min were associated with increased risk of all-cause death compared with those with MEE below 178 kcal/min.ConclusionARNI significantly reduced MEE compared with ACEI/ARB. MEE was significantly associated with the severity of left ventricular systolic dysfunction and long-term prognosis. An MEE value over 178 kcal/min was a powerful predictor of cardiac death and linked with increased risk of 1-year all-cause mortality in patients with AMI complicated by HF.